Development and survival of infective larvae of nematode parasites of sheep on pasture in a cool tropical environment - Tembely, S. (Elsevier, 1998)
The development and survival of nematode parasites of sheep were studied in a cool tropical environment of the highlands of Ethiopia on 24 plots serially contaminated with Haemonchus contortus, Longistrongylus elongata and Trichostrongylus colubriformis eggs over a period of 2 consecutive years from June 1993 to May 1995. The availability of infective larvae was monitored by monthly pasture sampling and larvae recovery. Infective larvae were recovered from the herbage collected from the plots contaminated in June, July, August, September and October of both years. The longevity of infective larvae varied between two and six weeks when eggs were deposited on pasture in June and October respectively. During the dry and short rainy season (November through May), eggs failed to develop into L3 stage. It is suggested that the long period (7 to 8 months) of lack of development of trichostrongylid infective larvae on the pasture can be efficiently used in a strategic treatment programme to interrupt transmission of H. contortus, L. elongata and T. colubriformis in sheep in this environment.